A Critical Discourse Analysis of Jakarta Massive Flood News in Kompas.Com - Putra Thoip Nasution; Didin Nuruddin Hidayat; Alek Alek (Al-Lisan: Jurnal Bahasa, 2021)
The potential of discourse analysis in interpreting written languages hasattracted linguists’ interest to further extend the discussion. This study aims toanalyze the headline news of Kompas.com about a massive Jakarta flood occurringin 2019 through the perspective of Critical Discourse Analysis (CDA). The studyemployed qualitative research descriptive using a Van Dijk’s framework consistingof three dimensions: macrostructure, superstructure, and microstructure. The datawere collected from Kompas.com online news entitled Banjir Jakarta: Normalisasiyang Terlambat dan hasil naturalisasi yang Belum Terlihat (Jakarta Flood: DelayedNormalization and Unseen Naturalization Results) (Kompas.Com, 2020). Thestudy found that Kompas.com used direct diction to present the text and took astand in the opposition to the Jakarta Governor policy. It was implicitly derivedfrom the sentences and paragraphs analyzed from CDA perspectives. The studyconcluded that the news provides information to readers and spread thought orunderstanding of the ideology adopted by journalists themselves.